Orthohantaviruses in Misiones Province, Northeastern Argentina - María Victoria Vadell; Eliana Florencia Burgos; Daniela Lamattina; Carla Bellomo; Valeria Martínez; Rocío Coelho; Cecilia Lanzone; Carolina Alicia Labaroni; Laura Tauro; Oscar Daniel Salomón; Isabel Elisa Gómez Villafañe (Emerging Infectious Diseases, 2024)
Few cases of hantavirus pulmonary syndrome have been reported in northeastern Argentina. However, neighboring areas show a higher incidence, suggesting underreporting. We evaluated the presence of antibodies against orthohantavirus in small rodents throughout Misiones province. Infected Akodon affinis montensis and Oligoryzomys nigripes native rodents were found in protected areas of Misiones.